Jaringan Aktor dalam Penanganan Perkara Korupsi oleh Kejaksaan: Pendekatan Social Network Analysis - Methodius Kossay (Universitas Sains dan Teknologi Komputer, 2026)
This study analyzes corruption case handling by the Prosecutor’s Office through a Social Network Analysis (SNA) within the framework of Network Governance Theory. It reconceptualizes prosecutorial performance as a networked enforcement system shaped by inter-organizational relations rather than a purely hierarchical legal process. The unit of analysis is case-based relational networks across investigation, prosecution, and audit stages. Findings indicate a moderately centralized but structurally fragmented network, where cross-institutional coordination is primarily mediated by brokerage actors. Centrality analysis reveals a clear decoupling between formal authority and relational power, with actors holding high betweenness centrality exerting disproportionate influence over information flow and evidentiary validation. Modularity results identify three institutional clusters—investigation, prosecution, and audit—with strong internal cohesion but weak inter-cluster connectivity. This configuration produces a brokerage-dependent enforcement structure, where case progression relies on a limited number of bridging actors. Network density further confirms asymmetric coordination patterns characterized by strong intra-cluster ties and weak inter-cluster integration. The study introduces the concept of configurational enforcement bias, highlighting how network structure systematically shapes prosecutorial outcomes through unequal distribution of information access and coordination capacity. The findings extend Network Governance Theory by demonstrating that criminal justice governance is structurally asymmetric and relationally contingent.